Kesiapan Pembiayaan Prabencana di Badan Penanggulangan Bencana Daerah (BPBD) Kota Palu - Napirah, Muhammad Ryman; Vidyanto; Sulaiman, Miftahul Haerati (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Disaster is an event or incident that threatens and disrupts people's lives.Objective: The purpose of this study was to analyze the readiness of pre-disaster financing in disaster risk reduction programs, disaster prevention programs, and disaster education at Palu City BPBD.Methods: This type of research is qualitative research with a case study approach. There are three informants in this study, namely key informants, ordinary informants, and additional informants. To obtain data, a technique is needed, therefore in this qualitative research the technique used is triangulation of techniques and sources.Results: The results showed that the budgeting for pre-disaster programs in Palu City is allocated annually, for the allocation of funds for disaster risk reduction programs is also the same. The budget for disaster prevention comes from the APBD and APBN, with or without a budget, Palu City BPBD can still run its disaster program. Disaster financing for disaster education programs at the Palu City BPBD comes from APBD and APBN funds.Conclusion: It is expected that financing for disaster risk reduction programs, disaster prevention programs, and disaster education at the Palu City BPBD must be allocated annually, and routine training must be carried out for staff.